2016
DOI: 10.1038/bjc.2016.267
|View full text |Cite
|
Sign up to set email alerts
|

Comparing desferrioxamine and light fractionation enhancement of ALA-PpIX photodynamic therapy in skin cancer

Abstract: Background:Aminolevulinic acid (ALA)-based photodynamic therapy (PDT) provides selective uptake and conversion of ALA into protoporphyrin IX (PpIX) in actinic keratosis and squamous cell carcinoma, yet large response variations in effect are common between individuals. The aim of this study was to compare pre-treatment strategies that increase the therapeutic effect, including fractionated light delivery during PDT (fPDT) and use of iron chelator desferrioxamine (DFO), separately and combined.Methods:Optical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 45 publications
3
34
1
Order By: Relevance
“…Coutier et al reported for mTHPC that illumination with a fluence rate of 30 and 5 mW·cm −2 did not change the intratumor pO 2 and resulted in a significant longer tumor growth delay compared to higher fluence rate illuminations [32]. The rate and extent of photobleaching can be used for implicit dosimetry [3,[10][11][12]. In the present study we observed a slower rate of photobleaching for high fluence rate illuminations of 50 and 150 mW·cm −2 compared illumination with 20 mW·cm −2 .…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Coutier et al reported for mTHPC that illumination with a fluence rate of 30 and 5 mW·cm −2 did not change the intratumor pO 2 and resulted in a significant longer tumor growth delay compared to higher fluence rate illuminations [32]. The rate and extent of photobleaching can be used for implicit dosimetry [3,[10][11][12]. In the present study we observed a slower rate of photobleaching for high fluence rate illuminations of 50 and 150 mW·cm −2 compared illumination with 20 mW·cm −2 .…”
Section: Discussionsupporting
confidence: 49%
“…Significantly less cell survival is observed using a fluence rate of 20 mW·cm −2 compared to 150 mW·c m −2 in-vitro and significant less tumors were cured after illumination with 150 mW·cm −2 or 50 mW·cm −2 compared to 20 mW·cm −2 in-vivo. It is well known that fluence rate is an important factor for therapeutic outcome of non-targeted PDT [3,4,10,12]. Illumination with a high fluence rate has shown to result in less tissue damage during 5-aminolevulinic acid based protoporphyrin IX PDT [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that fractional (that is,intermittent) treatment with light might be as uperior approach to obtain more potent PDT effects as ac onsequence of reduced short term O 2 consumption during the PDT process. [67][68][69][70] To further enhance fractional PDT,T uran et al recently developed an interesting boron-dipyrromethene (BODIPY)based PS. [71] In this system, BODIPY is incorporated with 2pyrdidone into as ingle bifunctional compound (PYR6).…”
Section: Fractional Pdtmentioning
confidence: 99%
“…Our results show that DFO enhances PpIX fluorescence in cell monolayers, but it does not when the same cells of adherent monolayer nature are forced into suspension. Different mechanisms, such as uptake rates, enzymatic activities or cell-to-cell interaction, have been identified as playing a role in the 5-ALA-induced PpIX photoactivation following exogenous DFO administration [24,35,36]. Yet, our attempt at enhancing the metabolic activities and maintaining membrane integrity did not increase the PPIX fluorescence of suspended cells any further.…”
Section: Discussionmentioning
confidence: 78%